(3LhGgQ GdYbhO ajeG jMJGL Edjg GdbVGg hGdTghOs - (3eMeO Hf CMeO Hf Ydj Hf YHO GdNGdb, TeS GdOjf GdSjhWj Ke GdbGgQj GdTGaYj GdefgGLj,J (B880 (3g` s
(3ChdgG (B:s
(3hHYO aEf JhbjY GdMce GdYRjR ejR bdHi GdYOd GdQGLM heMLI GdUOb hGdJi Sdhc fgLgG Gdbhje ef GcHQ GdeUGdM s
(3BNQgG (B:s
(3ZPG cGf GdSaQ WhjdkG Ch WGf VYjakG dG jbOQ Ydi GdeTi bHdg GdefUhH GdeTGQ Zdjg bHhdgG hjcd HGdETgGO hGdJGQjN hGdgd G(B'(3de Je GdLRA GdChd ef cJGH LhGgQ GdYbhO HMeO Gddg JYGdi hYhfg jJdhg ai GdLR AGdKGfi cJGH GdfcGM heG jJYdb Hg ef GdGMcGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B334 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B297s
Keywords: (3Gdabg GdESdGejs